2021
DOI: 10.1002/ar.24836
|View full text |Cite
|
Sign up to set email alerts
|

External reproductive structures of male Surfperches (Embiotocidae): Urogenital papilla

Abstract: Fishes exhibit a dynamic array of reproductive diversity. Among the various forms of reproduction, internal fertilization has evolved at least 13 times and has been observed in 2–3% of teleost species, half of which are marine. Internal fertilization has led to the evolution of male intromittent organs to aid in sperm transfer during copulation. The intromittent organs of poeciliids have been widely investigated, but little research has focused on the intromittent organs of marine fishes. The surfperches are i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The male rockfish has a UGP to ensure the safe transfer of sperm to the female (Iida, 2019). Previous studies have shown that the morphology of male external genitalia varies among taxa (Bond & Forsgren, 2022). In some bony fishes, specifically poeciliids and anablepids, the external genitalia develop from the median anal fin in the form of intromittent organs or genitalia (Rosa-Molinar & Burke, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The male rockfish has a UGP to ensure the safe transfer of sperm to the female (Iida, 2019). Previous studies have shown that the morphology of male external genitalia varies among taxa (Bond & Forsgren, 2022). In some bony fishes, specifically poeciliids and anablepids, the external genitalia develop from the median anal fin in the form of intromittent organs or genitalia (Rosa-Molinar & Burke, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Males of viviparous teleost fish have evolved special intromittent organs that protrude externally from the reproductive tract and transport sperm into females for internal fertilization. The shift from external to internal fertilization in teleost fishes has led to changes in the sperm transfer mechanism correlated with the evolution of intromittent organs (Bond & Forsgren, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most teleosts (about 97%) exhibit external fertilization, in which males and females release gametes into the water [1]. Teleosts with internal fertilization have evolved different mating apparatuses for sperm transport in males in order to survive and reproduce [2]. These are mostly fin specializations or external extensions of the reproductive tract.…”
Section: Introductionmentioning
confidence: 99%